Numerical method for solving the dirichlet boundary value problem for nonlinear Triharmonic equation - A, Dang Quang; Nguyen Quoc, Hung; Vu Vinh, Quang (Journal of Computer Science and Cybernetics, 2022)
In this work, we consider the Dirichlet boundary value problem for nonlinear triharmonic equation. Due to the reduction of the problem to operator equation for the pair of the right hand side function and the unknown second normal derivative of the function to be sought, we design an iterative method at both continuous and discrete levels for numerical solution of the problem. Some examples demonstrate that the numerical method is of fourth order convergence. When the right hand side function does not depend on the unknown function and its derivatives, the numerical method gives more accurate results in comparison with the results obtained by the interior method of Gudi and Neilan.